Analisa Penerimaan Pengguna e-wallet Sebagai Transaksi Digital Menggunakan Metode TAM (Technologi Acceptance Model) - Siahaan, Heppy Rosalina; Budihartanti, Cahyani (Journal of Computer Science and Engineering (JCSE), 2023)
As technology advances and digital transactions continue to grow, many companies are now launching digital or cashless transaction applications. This allows users to be more selective in choosing a digital or cashless transaction application, also known as an e-wallet, that they want to use. Factors considered in this selection process include ease of use, offered features, transaction speed, security, and the number of merchants available. This research aims to provide users with information to choose a high-demand e-wallet by implement the Technology Acceptance Model (TAM) to calculate the selection of a high-demand digital wallet. Based on the data calculated using the TAM method and survey results that include appearance criteria, offered items, convenience, security, and the number of merchants, GO-PAY is considered the primary alternative for a digital wallet with a demand rate of 47.8%. OVO comes in second place with 31.1%, followed by DANA in the last position with 21.1%